QUALITY MANAGEMENT: EFFORTS AND PROBLEMS IN ETHIOPIAN MANUFACTURING INDUSTRIES - Kitaw, Daniel; Bete, Fasika (Zede Journal of Ethiopian Engineers and Architects, 2023)
This paper deals with the analysis and the current quality management practices in Ethiopian manufacturing industries. The research is based on a survey conducted on 55 representative industries all over the country. A brief introduction is given on the fundamental concepts of quality with reference to the recent literature in the area so as to help readers follow the model developed The quality problems of the industries and the root causes that trigger them have been analyzed by employing a well structured questionnaire. Then a quality management implementation model is developed along with the step-by-step approach to attain the goal. Finally a number of recommendations are given at individual level, institutional level and at a national level. This paper may also be considered as a summary of the existing situation and a lead for future researches in thefield